Implementasi Aplikasi ClassPoint dalam Pembelajaran Bahasa Indonesia Materi Teks Novel Kelas XII MA Negeri 1 Serang (Metakognisi, 2025)
The rapid development of technology leads people to always learn about the latest developments. One of the updates taking place in education is by utilizing digital, namely the ClassPoint application, in the learning process. In this regard, the research aims to determine the implementation of ClassPoint in class 12 novel material which discusses intrinsic element analysis. Research is included in qualitative descriptions. The research subjects were class The research was conducted at MA Negeri 1 Serang for 2 weeks and was carried out in class Research regarding the application of ClassPoint as a learning medium includes two things 1) teacher presentation media in class, 2) assessment and evaluation media. Apart from that, the research also reviews the advantages and disadvantages of ClassPoint in novel learning. Furthermore, the research results showed that 84.19% of the questionnaire responses from class 12 IPS students at MA Negeri 1 Serang showed that students felt satisfied and motivated regarding the implementation of learning using the ClassPoint application.  Apart from that, students also feel active in class when using the ClassPoint application because it is very easy to understand.
Keywords: Keywords: Implementation, Learning Media, Classpoint